Securing of mineral resources in spatial and regional planning - Hartz, Andrea; Saad, Sascha; Schniedermeier, Lydia; Fleischhauer, Mark; Greiving, Stefan (Raumforschung und Raumordnung | Spatial Research and Planning, 2018)
Mineral resources are used in virtually all branches of production. The extraction of resources is competing with other land uses and often meets little acceptance. Spatial planning plays an important role not only for precautionary land use for resource extraction, but also for long-term securing of resource potentials. The spatial planning involves a weighing against other land uses and functions in the sense of a sustainable regional development. This paper looks into the question how the statewide and regional planning meets this requirement with regard to non-energetic mineral resources. The results of polls and plan analyses show massive variations in the regulatory scope for securing resources in the statewide and regional plans. This serves as a basis on which solutions are highlighted for an adequate consideration of securing resources in spatial planning. These relate to the methodical challenges in the weighing process as well as the design of the spatial planning toolsets.
Keywords: Mineral resources; Spatial planning; Resource extraction; Securing resources; Subsequent uses